Analysis of Factors Affecting Income Smoothing Among Listed Companies in Indonesia - Sherlita, Erly; Kurniawan, Putri (Sains Humanika, 2013)
This study examines the factors that influence income smoothing practice, such as firm size, profitability, financial leverage, and net profit margin. Grouping among the companies that perform income smoothing, and that does not do income smoothing using Eckel index to net income for the manufacturing companies listed on the Indonesian Stock Exchange. The research sample totaling 68 companies with a sub-sample of 204 financial reports. Observations were made during the three years, from 2008 to 2010. Statistical analysis using binary logistic regression to determine the factors that influence income smoothing. The results showed that the variables of profitability and net profit margins have significant differences between smoothing company profits by not smoothing profits, while the variable firm size and financial leverage has no significant difference. Test results using a multivariate binary logistic regression either simultaneously or separately on the four independent variables thought to affect the practice of income smoothing apparently no one has proved influential. Thus it can be concluded that firm size, profitability, financial leverage, and net profit margin has no effect on the practice of income smoothing.